ダイ 26 ジ ナンキョク チイキ カンソク タイ デ ウチアゲル オーロラ タンサ ロケット カンソク ケイカク - 山岸, 久雄; ヤマギシ, ヒサオ; 福西, 浩; フクニシ, ヒロシ; Yamagishi, Hisao; Fukunishi, Hiroshi (1985)
P(論文) 第26次南極地域観測隊越冬隊では国際中層大気観測計画(MAP)に呼応して, 1985年の冬季に2機のオーロラ探査ロケットを打ち上げる計画である。この観測はオーロラ発光高度での波動-粒子相互作用の過程を明らかにすることを目的としている。この論文では観測計画の概要を述べる。 It is scheduled that two sounding rockets are launched from Syowa Station, Antarctica in the austral winter of 1985 as part of the international Middle Atmosphere Program (MAP), by the wintering party of the 26th Japanese Antarctic Research Expedition. This experiment aims at the study of the wave-particle interaction processes on auroral field lines. The present paper gives an outline of the mission plan of the experiment. departmental bulletin paper